Complement Factor C4d Is a Common Denominator in Thrombotic Microangiopathy - Chua, Jamie S.; Baelde, Hans J.; Zandbergen, Malu; Wilhelmus, Suzanne; van Es, Leendert A.; de Fijter, Johan W.; Bruijn, Jan A.; Bajema, Ingeborg M.; Cohen, Danielle (Journal of the American Society of Nephrology, 2015)
Complement activation has a major role in thrombotic microangiopathy (TMA), a disorder that can occur in a variety of clinical conditions. Promising results of recent trials with terminal complement-inhibiting drugs call for biomarkers identifying patients who might benefit from this treatment. The primary aim of this study was to determine the prevalence and localization of complement factor C4d in kidneys of patients with TMA. The secondary aims were to determine which complement pathways lead to C4d deposition and to determine whether complement activation results in deposition of the terminal complement complex. We examined 42 renal sections with histologically confirmed TMA obtained from a heterogeneous patient group. Deposits of C4d, mannose-binding lectin, C1q, IgM, and C5b-9 were scored in the glomeruli, peritubular capillaries, and arterioles. Notably, C4d deposits were present in 88.1% of TMA cases, and the various clinical conditions had distinct staining patterns within the various compartments of the renal vasculature. Classical pathway activation was observed in 90.5% of TMA cases. C5b-9 deposits were present in 78.6% of TMA cases and in 39.6% of controls (n=53), but the staining pattern differed between cases and controls. In conclusion, C4d is a common finding in TMA, regardless of the underlying clinical condition. Moreover, C5b-9 was present in >75% of the TMA samples, suggesting that terminal complement inhibitors may have a beneficial effect in these patients. C4d and C5b-9 should be investigated as possible diagnostic biomarkers in the clinical work-up of patients suspected of having complement-mediated TMA.